The aged nonhematopoietic environment impairs natural killer cell maturation and function. Issue 2 (9th February 2015) - Shehata, Hesham M.; Hoebe, Kasper; Chougnet, Claire A.
Summary Natural killer (NK) cells are critical in eliminating tumors and viral infections, both of which occur at a high incidence in the elderly. Previous studies showed that aged NK cells are less cytotoxic and exhibit impaired maturation compared to young NK cells. We evaluated whether extrinsic or intrinsic factors were responsible for the impaired maturation and function of NK cells in aging and whether impaired maturation correlated with functional hyporesponsiveness. We confirmed that aged mice have a significant decrease in the frequency of mature NK cells in all lymphoid organs. Impaired NK cell maturation in aged mice correlated with a reduced capacity to eliminate allogeneic and B16 tumor targets in vivo. This could be explained by impaired degranulation, particularly by mature NK cells of aged mice. Consistent with impaired aged NK cell maturation, expression of T‐bet and Eomes, which regulate NK cell functional maturation, was significantly decreased in aged bone marrow (BM) NK cells. Mixed BM chimeras revealed that the nonhematopoietic environment was a key determinant of NK cell maturation and T‐bet and Eomes expression. In mixed BM chimeras, NK cells derived from both young or aged BM cells adopted an 'aged' phenotype in an aged host, that is, were hyporesponsive to stimuli in vitro, while adopting a 'young' phenotype following transfer in young hosts. Overall, our data suggest that the aged nonhematopoietic environment is responsible for the impaired maturation and function of NK cells. Defining these nonhematopoietic factors could have important implications for improving NK cell function in the elderly.